THE IMPACT OF THE USE OF PETICIDES AND PARAQUANT IN PT INCASI RAYA SJAL FOR THE WORKERS AND THE ENVIRONMENT - Fani Yusfita Sari (Pendidikan IPA, FMIPA, UNP, 2022)
Indonesia is a developing country that has abundant natural resources, especially palm oil. In Indonesia, a lot of forests are made into oil palm plantations and palm oil mills have been spread throughout Indonesia, one of which is PT Incasi Raya SJAL Lunang Silaut. Here many workers work from the office sector to the fertilization sector. Here they use chemicals that we often hear, namely pesticides . Despite their adverse effects on humans and the environment, pesticides,including herbicides, are often used in oil palm plantations.Paraquat Has been used for more than 40 years in both large and small plantations, paraquat dichloride, known simply as 'paraquat', is one of the most widely used herbicides in the world. In Indonesia, 'paraquat' is sold under the name Gramoxone.According to the World Health Organization (WHO), there are not 20,000 people per year, due to pesticide poisoning. It is estimated that 5,000 - 10,000 people per year experience a very fatal impact, such as experiencing cancer, disability, infertility and liver disease.Here will discuss how the impact will occur if workers do not use safety equipment at work and how to use chemicals properly.not only bad for humans, these pesticides and paraquants are also bad for the environment because if they are used excessively they will reduce soil fertility and plant growth is not normal.